2020
DOI: 10.1111/brv.12581
|View full text |Cite
|
Sign up to set email alerts
|

Are we overestimating risk of enteric pathogen spillover from wild birds to humans?

Abstract: Enteric illnesses remain the second largest source of communicable diseases worldwide, and wild birds are suspected sources for human infection. This has led to efforts to reduce pathogen spillover through deterrence of wildlife and removal of wildlife habitat, particularly within farming systems, which can compromise conservation efforts and the ecosystem services wild birds provide. Further, Salmonella spp. are a significant cause of avian mortality, leading to additional conservation concerns. Despite numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 302 publications
(353 reference statements)
8
98
2
1
Order By: Relevance
“…prevalence in both our environmental faecal samples (13.1%) and mist-net samples (10.2%) than Smith, Snyder, et al (2020) found in their meta-analysis collating prevalence estimates across species (27%), including their estimate for passerines (28%), which formed the majority of our samples. The estimate reported by Smith, Snyder, et al (2020) was likely inflated due to the majority of past research focusing on a small number of synanthropic species. For example, Hald et al (2016) found an overall Campylobacter spp.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…prevalence in both our environmental faecal samples (13.1%) and mist-net samples (10.2%) than Smith, Snyder, et al (2020) found in their meta-analysis collating prevalence estimates across species (27%), including their estimate for passerines (28%), which formed the majority of our samples. The estimate reported by Smith, Snyder, et al (2020) was likely inflated due to the majority of past research focusing on a small number of synanthropic species. For example, Hald et al (2016) found an overall Campylobacter spp.…”
Section: Discussionmentioning
confidence: 66%
“…These 'buyer agreements' are assumed to improve food safety but are based on few data, including a few sensationalized outbreaks linked to wildlife (Beretti & Stuart, 2008;Gardner et al, 2011;Karp et al, 2015;Smith, Snyder, et al, 2020). Importantly, our finding that Campylobacter spp.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It is responsible for disease in humans and many mammalian and avian livestock species, including cows, pigs, goats, sheep, and poultry of all types. Concerns about starlings focus mainly on the spread of Salmonella among livestock and poultry, though direct transmission to humans via fecal matter in human food crops [ 28 ] or urban areas is also a potential concern [ 46 ]. For livestock, the concern is both economic loss due to animal illness, and secondarily, transmission to humans via contaminated products (meat, eggs, dairy products, etc.).…”
Section: Resultsmentioning
confidence: 99%